The diversity of leaves and asiaticoside content on three accessions of Centella asiatica with the addition of chicken manure fertilizer (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Mumtazah HM, Supriyono, Widyastuti Y, Yunus A. 2020. The diversity of leaves and asiaticoside content on three accessions of Centella asiatica with the addition of chicken manure fertilizer. Biodiversitas 21: 1035-1040. Centella asiatica (L.) commonly known as an essential medicinal herb. This plant has high diversity, especially in leaf morphology. The main objective of this research was to determine the morphology of leaves and the effect of chicken manure dosage on the increase of asiaticoside content. The leaves of three accessions characterized, and then C. asiatica planted. The research design used a completely randomized design (CRD) factorial, with the first factor is accession (C) with 3 levels (C1: accession 1, C2: accession 2, C3: accession 3). The second factor was chicken manure with 4 levels dosage (P1: 0 ton ha-1, P2: 10 tons ha-1, P3: 15 tons ha-1 and P4: 20 tons ha-1). Asiaticoside analysis used the TLC method with chloroform: methanol: water (65:25:4) as mobile phase. The result from this research showed that the diversity in leaf morphology of three accessions is in leaf size and petiole length. Accession 3 has the widest leaf size (7.3 cm) and the longest petiole (9.8 cm), accession 2 with a leaf width of 5.8 cm and petiole length in 8.5 cm, while the accession 1 has the least leaf width (5.3 cm) and the length of the petiole is the shortest with 7.3 cm. Observation results of asiaticoside showed that the highest content of asiaticoside produced by accession 3 (0.19%), then accession 1 with a content of 0.15%, while accession 2 showed the lowest asiaticoside content (0.13%). The treatment of chicken manure addition significantly increase asiaticoside content in accessions 1 and 3, but in accession 2 it was not significantly increased. The highest content of asiaticoside (0.34%) were in accession 3 with the addition of chicken manure 20 tons ha-1 (P4).
Keywords: Accession, asiaticoside, Centella asiatica, chicken manure, diversity